New business strategies of football clubs - András , Krisztina; Havran, Zsolt (Applied Studies in Agribusiness and Commerce, 2015)
The study investigates new strategies of football clubs in function of last few years’ trends in European football leagues. There were many changes in international professional football during the last 10-15 years that had significant effect on the success of certain clubs. We show empirical evidences about these effects based on data about revenues, transfer balance, financial and sport successes. We focus on Western European leagues and classify clubs based on their business and sport strategies.